Pengaruh CR, DER, dan NPM terhadap Harga Saham Pada Trade Service Tahun 2014-2018 - Santy Santy; Novita Ira Yanni Purba; Suryani Nduru; Aldi Pratama; Wirda Lilia (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This research has objective to know the influence of current ratio, debt to equity ratio, net profit margin on the price of shares in the trade and investment service at the Indonesian stock exchange in the period of 2014-2018. The data used sourced from the data at the Indonesian stock exchange through www.idnfinancials.com, and has been done selection based on set criteria. This research is expected to allow can be a science to help the researchers next and also students or people who needs a source of information. From the research it can be seen that the Current ratio, Debt to equity ratio partially influences and experiences a significant effect on stock prices. Net profit margin partially has no effect and does not experience a significant effect on stock prices on Trade service and investment. But all variables affect simultaneously.